The Consumption Behavior of K-Pop Fans from the Perspective of Maslahah - Awan, Edi; Khalida, Nur Diana; Firdaus, Jannatul; Saniatin, Any; Najiatun, Najiatun; Fauziyah, Hanifah (Juwara: Jurnal Wawasan dan Aksara, 2025)
This study examines the consumption behavior of K-Pop fans from the perspective of maslahah in Islamic economics. The main problem raised is the imbalance between the fulfillment of needs and desires, and how it is relevant to the concept of welfare according to Islamic law. The purpose of this study is to analyze whether the consumption behavior of K-Pop fans reflects the principles of maslahah which emphasize the balance between worldly satisfaction and the blessings of the hereafter. This study uses a descriptive-analytical approach with qualitative methods. Data were collected through observation and interviews with a number of K-Pop fans in the author's environment as research samples. The results of the study indicate that consumption that is oriented solely to the fulfillment of desires tends to be inconsistent with the principles of maslahah, because it ignores the spiritual aspects and social responsibility in Islam. The implications of this finding emphasize the importance of awareness of Islamic values in forming consumption behavior that is not only materially satisfying, but also has worship value and supports the achievement of true welfare.